Estudo da interação genótipo x ambiente e validação de marcadores microssatélites associados a QTLs para conteúdo de óleo e proteína em soja - Souza Neto, José Dias de (2015)
Soy is one of the most important crops worldwide due to the oil and extracted protein from its seeds. Due to this importance, our objective was the evaluation of strains of soybean, from Quality Breeding program at UFV in the state of Minas Gerais, from oil and protein content as well as adaptability and stability of the lines in three environments, the latter being evaluated by the methods of Eberhart and Russell and Centróides. Also, we aimed to select SSR markers associated with QTLs for oil content and protein in these strains. A total of 56 locus of SSR markers, were used. Regarding the analysis of adaptability and stability, the strains 13, 18, 90, 148, 152,172, 204, 206, 174 and 120. We selected for oil content, and the lines 124, 158 and 143, for protein. The grouping analysisformed 21 groups of 208 limhagens, with 92,184, 6101 and 192 Msoy showing greater dissimilarity genotype. The association analyzes did not reveal any association at 1 and 5% significance level using the Bonferroni correction. However, allele 3 was selected alleles in marker 239, and alleles 1 and 2 at Satt 539, for oil, while allele 1 at Satt 263, and allele 3 at Satt 463 for protein content.